EFISIENSI PEMASARAN KOPI (Coffea sp) DI KECAMATAN SINGOROJO KABUPATEN KENDAL - Sujiwo, Joko Tri; Wahyuningsih, Sri; Supardi, Suprati (MEDIAGRO, 2009)
Coffee (Coffea sp) constitutes an important commodity for most local areas in Kendal Regency, including the District of Singorojo. Marketing efficiency was very needed by the coffee farmers in Singorojo District in order to sell their coffee. This research was intended to find out: (1). the efficiency in marketing the coffee by the District of Singorojo  Kendal Regency, (2). the volume of sales of the coffee by the District of Singorojo Kendal Regency, (3). the attempts by the coffee farmers in the District to make the marketing of the coffee more efficient. This research used a descriptive-analytical method. The analyses on the purchasing prices, the selling prices and the profits obtained by the parties involved in this District has been efficient, with big sellers constituted the ones who got the biggest profits. There were two channels for marketing the coffee produced in the District of Singorojo. First channels for marketing that is the coffee farmers, big sellers, and exporter. Second channel for marketing that is the coffee farmers, small sellers, big sellers, and exporter. The volume of sales of the coffee by the District of Singorojo Kendal Regency high enough. The average sale of coffee by the farmers in this Singorojo district was 712,72 kilogram coffee or equal to 97,49 %. In order to reduce the marketing chains for the coffee, the coffee farmers  in the District has established GAPOKTAN (a Farmer Association).